Hubungan Antara Jenis Kelamin, Uang Jajan, Kebiasaan Sarapan, Kebiasaan Membawa Bekal, Dan Pengetahuan Gizi Dengan Perilaku Siswa Memilih Makanan Jajanan Di SDN Keraton 1 Martapura - Norhasanah Norhasanah; Firyal Yasmin; Nur Azizah Hestyani (Jurnal Kesehatan Indonesia, 2018)
School-aged children have habit to eating hawker foods. Hawker foods are less qualified health and nutrition, so it will health threats to children The study aimed to find out the correlation between gender, pocket money, habitual breakfast and bringing packed meal and nutrition knowledge with the student behaviors on choosing hawker foods. This study type was observational with Cross Sectional approach. This study population was 49 children. The study results that the children’s knowledge level on choosing hawker food, mostly of them had good knowledge of 53%. The gender of student behaviors chose the best hawker foods of 32,7%. Pocket money of student behaviors chose the best hawker foods of 32,7%. Habitual breakfast of student behaviors chose the best hawker foods of 51%. The habitual bringing pack meal of student behaviors chose the best hawker foods of 22,4%. Based on Rank Spearman correlation analysis, that there was no relation between children's knowledge and choosing hawker food (value p = 0,165), There was no relation between sex and choosing hawker food (p value = 0,482), no relation between pocket money and choosing hawker food (value p = 0,127), there was no relation between the habitual bringing packed meal and the choosing hawker food (p = 0, 495), there was relation between habitual breakfast and choosing hawker food (p = 0,030 )